2022
DOI: 10.1049/bsb2.12043
|View full text |Cite
|
Sign up to set email alerts
|

Topographical biointerface regulating cellular functions for bone tissue engineering

Abstract: The physiochemical properties of the implant interface significantly influence cell growth, differentiation, cellular matrix deposition, and mineralisation, and eventually, determine the bone regeneration efficiency. Cells directly sense and respond to the physical, chemical, and mechanical cues of the implant surface, and it is increasingly recognized that surface topography can evoke specific cellular responses, conferring biological functions on substrate materials and regulating tissue regeneration. Curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 193 publications
(267 reference statements)
0
8
0
Order By: Relevance
“…It is commonly accepted that manipulating the topographical factors of matrices could regulate cell behavior including cell morphology and orientation. [ 37 ] To determine the influence of alignment topography and 3D configuration of nanofibers on cell morphology, both seeded‐scaffolds were stained after 7 days of culture. The cytoskeleton was stained red with FITC‐conjugated phalloidin, and the nucleus was stained blue with DAPI.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is commonly accepted that manipulating the topographical factors of matrices could regulate cell behavior including cell morphology and orientation. [ 37 ] To determine the influence of alignment topography and 3D configuration of nanofibers on cell morphology, both seeded‐scaffolds were stained after 7 days of culture. The cytoskeleton was stained red with FITC‐conjugated phalloidin, and the nucleus was stained blue with DAPI.…”
Section: Resultsmentioning
confidence: 99%
“…Cells recognize and respond to contact guidance cues, which extend to nanoscale topographical features. [ 37,57 ] Such alignment topography of nanofibers is deemed to be an ideal substrate for facilitating the regeneration of tissues with similar structures, like tendons, ligaments, nerve, cardiac, and skeletal muscles, since they can convey topographical cues to cells and consequently promote higher expression of the corresponding markers, as reported by several researchers. [ 2,73 ] Thus, the promotion of MSCs toward tendon lineage on EPU mats and EPU bundles compared to TCP could be attributed to the alignment topography of nanofibers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address the common issue of metal implant loosening and negative reactions to material implantation, it is necessary to develop an innovative biomaterial. The titanium‐based implant should be accompanied by a microenvironment that supports osteogenic differentiation and anti‐inflammatory responses, thereby facilitating bone regeneration and osseointegration 21,22 . Studies have shown that bioactive substances such as RGD, OGP, and ECM play a crucial role in bone regeneration by stimulating osteoblast proliferation, differentiation, alkaline phosphatase activity, collagen secretion, and matrix mineralization 23–25 …”
Section: Discussionmentioning
confidence: 99%
“…Figure 7A, C inflammatory responses, thereby facilitating bone regeneration and osseointegration. 21,22 Studies have shown that bioactive substances such as RGD, OGP, and ECM play a crucial role in bone regeneration by stimulating osteoblast proliferation, differentiation, alkaline phosphatase activity, collagen secretion, and matrix mineralization. [23][24][25] In this study, a layer-by-layer self-assembly technique was employed to modify the surface of titanium-based materials with MC3T3-E1 protein.…”
Section: Analysis Of Osteogenic Capacitymentioning
confidence: 99%